On Strategic Assumption-Making: A Dialectical Approach to Policy and Planning - Mitroff, Ian I.; Emshoff, James R. (Academy of Management Review, 1979)
This article attempts to develop a new methodology for dealing with ill-structured (i.e., ill-defined, messy) organizational problems, arguing that conflict, assumption surfacing, and assumption challenging are central to such a methodology. As such, the methodology for ill-structured problems is very different from that for well-structured ones. The methodology is illustrated through the analysis of an actual case.